Ecocultural ethics : critical essays - Alex, Rayson K. (Ecocritical theory and practice., 2017)
The book provides ecocultural perspectives on ethics from a variety of cultural contexts. It argues that any ecological perspectives/issues/conditions cannot be separated from their cultural contexts and thus, we need to employ a culture-specific scrutiny to understand the ethics of ecoculture.